Ultrasensitive PEC aptasensor based on one dimensional hierarchical SnS2|oxygen vacancy-WO3 co-sensitized by formation of a cascade structure for signal amplification - Zhang, Si; Zheng, Hejie; Jiang, Renjun; Yuan, Jiangfeng; Li, Fen; Qin, Tengteng; Sakthivel, Arunkumar; Liu, Xiaoqiang; Alwarappan, Subbiah (Sensors and actuators. B, Chemical, 2022)
Herein, we developed a photoelectrochemical (PEC) aptasensing platform that relies on a dual-signal amplification strategy. The proposed PEC system consists of a one dimensional (1D) hierarchical SnS2|OV (oxygen vacancy)-WO3 nanorods (NRs) sensitized by CdS quantum dots (QDs)/TCPP (TCPP: meso-tetra(4-carboxyphenyl)-porphine), and exonuclease III-assisted target recycling. As a photoactive heterojunction, SnS2|OV-WO3 nanocomposite exhibits a PEC signal ~11 times higher than pure WO3 NRs due to the enhanced separation efficiency of photo-generated carriers. Moreover, it was also used to immobilize a hairpin DNA3 probe labeled with CdS QDs/TCPP, which formed a co-sensitization cascade structure with SnS2|OV-WO3 NRs on the sensor surface due to the well-matched energy levels. This special cascade structure effectively shortened the electron-transfer path and inhibited charge recombination, thereby improving the PEC performance. The addition of the target vascular endothelial growth factor 165 (VEGF165) triggered the exonuclease III-assisted target recycling to generate plentiful DNA sequences (S1). S1 was specifically hybridized with HP3 to unfold its hairpin structure. As a result, CdS QDs/TCPP detached from the sensor surface and SnS2|OV-WO3 NRs, which destructed the co-sensitization cascade structure and minimized the PEC signals. The proposed PEC aptasensor exhibited a dynamic determination range of 0.5 fM-10 nM, and a detection limit of 0.34 fM for VEGF165. [Display omitted] •SnS2 nanoflakes are grown on OV-WO3 NRs to form a 1D hierarchical nanostructure.•SnS2|OV-WO3 exhibits a 11 times higher PEC signal than WO3 due to OVs and heterostructure formation.•CdS QDs/TCPP forms co-sensitization cascade structure with SnS2|OV-WO3.•A PEC aptasensor is designed based on the cascade structure combined with exonuclease III-assisted target recycling.•The aptasensor exhibits a detection limit of 2.4 fM for VEGF165.